Feminist criminology and technopolitics - Fernanda Martins (Oñati Socio-Legal Series)
In this article, based on the debates of feminist criminology in Brazil, we aim to analyze feminist campaigns that use technopolitics as a strategy to face gender violence. These campaigns are exposed through the disputes between emancipatory and punitive claims. We propose to use hashtags as feminist analysis tools to understand the ambivalence present in vulnerability. In order to do so, we will use the hashtags #ChegaDeFiuFiu, #MeuPrimeiroAssedio, and #MeuAmigoSecreto to analyze new meanings of justice promoted by the feminist movements, which appear not to prioritize the use of punitive power. In the same way, we seek from the #EleNão movement, recognized as feminist democratic technopolitics, to reformulate the possibilities of analyzing the Brazilian criminological field.